Clinical signs in cornea and ocular surface - Cosar, C. Banu; Sridhar, Mittanamalli S. (MEDKNOW PUBLICATIONS \& MEDIA PVT LTD, 2018)
A careful examination of cornea and ocular surface eliciting the basic signs will help a clinician toward an accurate diagnosis. Flipping the upper lid or pulling the lower lid to look at the inferior fornix may help to pick up any subtle clinical sign. Meticulous documentation by diffuse and slit view will help in following up the disease. Eyelids and ocular surface are evaluated externally and by slit lamp. Slit-lamp examination with the use of the stains such as fluorescein, rose bengal, or lissamine green provides extensive knowledge about the ocular surface. Tests of tear production are also detailed herein. This review is intended to help the eye practitioners in eliciting common clinical signs seen in cornea and ocular surface diseases.
Keywords: Clinical signs; cornea; corneal diagram; follicles; papillae; tear film